2023
DOI: 10.3390/w15203701
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Groundwater Quality and Contamination Using the Groundwater Pollution Index (GPI), Nitrate Pollution Index (NPI), and GIS

Hefdhallah S. Al-Aizari,
Fatima Aslaou,
Ali R. Al-Aizari
et al.

Abstract: Groundwater is an essential and indispensable resource, meeting dire needs for drinking and irrigation purposes. The aim of this study is to assess the suitability of groundwater quality for drinking purposes. This evaluation will be conducted using the Groundwater Pollution Index (GPI), the nitrate pollution index (NPI), and the geographic information system (GIS) in Sidi Slimane, Morocco. In this study, a comprehensive collection of 20 samples was obtained from various locations for analysis and evaluation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…Synthetic pollution index (SPI) and the water quality index (WQI) are among the most often used methods for classifying and reflecting the quality of the water and pollution risk in a given area. WQI and SPI have been utilized by researchers from several countries to evaluate the water quality in various places 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic pollution index (SPI) and the water quality index (WQI) are among the most often used methods for classifying and reflecting the quality of the water and pollution risk in a given area. WQI and SPI have been utilized by researchers from several countries to evaluate the water quality in various places 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The PIG, devised by Subba Rao in 2012 [34], presents a methodological approach to evaluate groundwater quality by assessing the influence of specific variables on its overall quality [35]. This index serves to gauge the relative impact on individual water quality parameters, as detailed in Table 1.…”
Section: Groundwater Quality: the Pollution Index Of Groundwater (Pig)mentioning
confidence: 99%
“…The wells close to the Sebou River and Nador Canal were the most polluted by nitrates from the study area. The findings from a study carried out in the Sidi Slimane region, Morocco [34], indicated that the pollution of water extracted from wells surpassed both Moroccan and global standards to a significant extent.…”
Section: Nitrate Pollution Index (Npi)mentioning
confidence: 99%
“…Consequently, it is strongly advised to not directly consume water from this area for drinking purposes. The findings from studies carried out in the Sidi Slimane and Sidi Allal regions [16,34] indicated that the pollution of water extracted from wells surpassed both Moroccan groundwater standards to a significant extent.…”
Section: Groundwater Pollution Index (Gpi)mentioning
confidence: 99%